1998
DOI: 10.1002/(sici)1097-4628(19980822)69:8<1471::aid-app1>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility of polystyrene with poly(ethylene oxide) and poly(ethylene glycol)

Abstract: ABSTRACT:The intrinsic viscosity of polystyrene-poly(ethylene oxide) (PS-PEO) and PS-poly(ethylene glycol) (PEG) blends have been measured in benzene as a function of blend composition for various molecular weights of PEO and PEG at 303.15 K. The compatibility of polymer pairs in solution were determined on the basis of the interaction parameter term, Db, and the difference between the experimental and theoretical weight-average intrinsic viscosities of the two polymers, D[h]. The theoretical weightaverage int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The cationic surfactant cetyl pyridinium chloride only interacts with high molecular weight PVP or poly(ethylene glycol) (PEG) 12. The viscosity of polystyrene (PS)–PEO and PS–PEG blends was measured in benzene as a function of the blend composition, and the interaction parameter used was the difference between the experimental and the theoretical values of the two polymers 13. Through viscometry, Ylmaz et al 14 showed that in dilute solutions, PS–PEO and polybutadiene‐ graft ‐polystyrene (PBS)–PEO are immiscible systems, and the miscibility parameter decreases with the increase in temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The cationic surfactant cetyl pyridinium chloride only interacts with high molecular weight PVP or poly(ethylene glycol) (PEG) 12. The viscosity of polystyrene (PS)–PEO and PS–PEG blends was measured in benzene as a function of the blend composition, and the interaction parameter used was the difference between the experimental and the theoretical values of the two polymers 13. Through viscometry, Ylmaz et al 14 showed that in dilute solutions, PS–PEO and polybutadiene‐ graft ‐polystyrene (PBS)–PEO are immiscible systems, and the miscibility parameter decreases with the increase in temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This was conducted to compare with the samples prepared from the organoclay and the intensive translucence, which was noticed with an increment of both the clay loadings and PEG contents. This is ascribed to the partial compatibility of the PS‐PEG blends . Although the blend system of the PS and PEG showed partial miscibility, the exfoliated nanocomposites were fulfilled by using the C10_P10 of the dry nanoclay gel formula to prepare the PS/clay nanocomposites via melt processing.…”
Section: Resultsmentioning
confidence: 99%